Identification and Mechanistic Studies of a Cell Cycle Regulator JP18 from a Library of Synthetic Indole Terpenoid Mimics. Issue 19 (2nd August 2016) - Pei, Jinpeng; Zhou, Shupeng; Yang, Fan; Sun, Yu; Li, Ang; Zhang, Wei‐Dong; He, Weiwei
Abstract: We constructed a small library of indole terpenoid mimics using a hybridizing strategy to link various indole and α, β‐unsaturated enone building blocks together. Prepared compounds were evaluated for the cytotoxicity against a panel of cancer cell lines. An indolyl ketone called JP18 was identified as a cell cycle regulator, and the underlying mechanism was investigated. Abstract : Regulators ! A small library of indole terpenoid mimics was evaluated for the cytotoxicity against a panel of cancer cell lines. An indolyl ketone JP18 from the library was identified as a cell cycle regulator, and the underlying mechanism was investigated.